Enhancing the anaerobic digestion of corn stover by chemical pretreatment with the black liquor from the paper industry. (June 2020) - Xu, Haipeng; Li, Yan; Hua, Dongliang; Zhao, Yuxiao; Mu, Hui; Chen, Honglei; Chen, Guanyi
Highlights: Black liquor pretreatment led to 59.1% increase in methane production. Methane production for 171.7 mL/g VS from organic components in the black liquor. Physical and chemical mechanism of methane yield improvement was analyzed. Whole slurry anaerobic co-digestion increased the buffering capacity of the digestate. No electrical conductivity inhibition or Na + inhibition happened. Abstract: In this work, black liquor as a waste from paper industry was used to pretreat corn stover before anaerobic digestion. The batch mode anaerobic digestion achieved a methane production up to 260.5 mL/g VS when the corn stover was pretreated the black liquor of 12 g NaOH/L alkalinity for 24 h, which was 59.1% higher than the control. In the semi-continuous mode anaerobic digestion, black liquor pretreatment increased the buffering capacity of the digestate to maintain suitable pH and total VFA/alkalinity ratio with no adverse effect resulted from the presence of ions. The structural and chemical changes of corn stover after the pretreatment were investigated to rationalize the enhanced performance of anaerobic digestion.